MODELING AND STUDY OF HYDROELECTRIC GENERATING SETS OF SMALL HYDRO POWER PLANTS WITH FREQUENCY-CONTROLLED PERMANENT MAGNET SYNCHRONOUS GENERATORS - R. I. Mustafayev; L. G. Gasanova; M. M. Musayev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2016)
Currently, the hydroelectric generating sets of small HPPs with Pelton turbines employ as their generating units conventional synchronous generators with electromagnetic excitation. To deal with the torque pulsatile behaviour, they generally install a supplementary flywheel on the system shaft that levels the pulsations. The Pelton turbine power output is adjusted by the needle changing water flow in the nozzle, whose advancement modifies the nozzle area and eventually – the flow. They limit the needle full stroke time to 20–40 sec. since quick shutting the nozzle for swift water flow reduction may result in pressure surges. For quick power adjustment so-called deflectors are employed, whose task is retraction of water jets from the Pelton turbine buckets. Thus, the mechanical method of power output regulation requires agreement between the needle stroke inside the turbine nozzles and the deflector. The paper offers employing frequency-controlled synchronous machines with permanent magnets qua generating units for the hydroelectric generating sets of small HPPs with Pelton turbines. The developed computer model reveals that this provides a higher level of adjustability towards rapid-changing loads in the grid. Furthermore, this will replace the power output mechanical control involving the valuable deflector drive and the turbine nozzle needles with electrical revolution rate and power output regulation by a frequency converter located in the generator stator circuit. Via frequency start, the controllable synchronous machine ensures stable operation of the hydroelectric generating set with negligibly small amount of water (energy carrier). Finally, in complete absence of water, the frequency-relay start facilitates shifting the generator operation to the synchronous capacitor mode, which the system operating parameter fluctograms obtained through computer modeling prove.